Polyfunkční objekt v Brně – příprava a organizace výstavby - Klevar, Lukáš (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Předmětem práce je příprava a organizace výstavby polyfunkčního objektu v Brně. Obsahem této práce je technologická zpráva, časový a finanční plán stavby, studie hlavních technologických etap, projekt zařízení staveniště, návrh a dimenze stavebních strojů, kontrolní a zkušební plány kvality a technologický předpis.

The subject of the work is the preparation and organization of construction multifunctional building in Brno. The content of this work is a technology report, time and financial plan of the building, the study of the main technological stages, the project construction site, design and dimensions of construction machinery, inspection and test plans for quality and technological regulation.
Multifunctional building in Brno-preparation and organization of construction
Keywords: Polyfunkční objekt; stavebně technologická zpráva; časový plán; rozpočet; harmonogram; ocelová konstrukce studie realizačních etap; stavební stroje; dimenze; etapy; technologické předpisy; plán kvality; zdroje; staveniště; dokumentace; objekt; náklady; doprava.; Multifunctional building; construction technology news; schedule; budget; schedule; steel structure study of implementation stages; construction equipment; dimensions; stages; technological regulations; quality plan; resources; construction sites; documentation; object; costs; transportation.